Respuesta :
To solve this, use the ‘completing the square’ strategy.
Leave a space to make the first two values a perfect square.
y=(x^2-2x___)-3
Divide -2 by 2 and square that number to put in the blank. Then subtract that number from outside.
y=(x^2-2x+1)-3-1
Simplify!
y=(x-1)^2-4
It is in vertex form now ;)
Please make my brainliest ,’-)
Leave a space to make the first two values a perfect square.
y=(x^2-2x___)-3
Divide -2 by 2 and square that number to put in the blank. Then subtract that number from outside.
y=(x^2-2x+1)-3-1
Simplify!
y=(x-1)^2-4
It is in vertex form now ;)
Please make my brainliest ,’-)
Answer: [tex]y=(x-1)^2-4[/tex]
Step-by-step explanation:
The vertex form of the equation of a parabola is:
[tex]y=a(x-h)^2+k[/tex]
Where (h,k) is the vertex.
To obtain this form, we need to complete the square:
Move the 3 to the other side of the equation:
[tex]y+3=x^2-2x[/tex]
Add this value to both sides of the equation: [tex](\frac{-2}{2})^2=1[/tex]
[tex]y+3+1=x^2-2x+1[/tex]
[tex]y+4=x^2-2x+1[/tex]
Then, rewriting:
[tex]y+4=(x-1)^2[/tex]
Finally, we must solve for "y", getting the equation of the parabola in vertex form:
[tex]y=(x-1)^2-4[/tex]